METHODS OF ASSESSMENT OF THE FINANCIAL MANAGEMENT EFFICIENCY OF AN ENTERPRISE UNDER THE VALUE CRITERION - Galina N. Ronova; Maxim S. Boronin (Статистика и экономика)
The authors discuss the value, as a fundamental criterion of innovative methods to assess the effectiveness of financial management of a company. Advantages and disadvantages are revealed. The authors proposed introduction of the value methods in the assessment process.